STRATEGIES FOR SUCCESSFUL FAMILY-OWNED BUSINESS - Zaki, Achmad; Rahayu, Mintarti; Susilowati, Christin (Universitas Brawijaya, Indonesia, 2018)
This study aimed at explaining the strategies of success in running family-owned enterprise to enable the next generation to develop the company which had been established by previous generations. This was a qualitative research with a case study approach conducted on military equipment business inTulungagung Regency. The results of this study indicated that the strategies of success in family-owned companies were through the process of selection of candidates for the next generation of the company and handing over all power to the elected candidates. Conflicts emerged inside the process of selection or determination of business leaders but through meetings orde liberation with all members of the second generation and produced an agreement that three of the six children of the family went into the organizational structure to manage the business. While the other three children set up their own business, however, the three children were still related to the development of family companies.